A Meshfree Approach for Bending Analysis of Porous Rectangular FGM Plate Resting on Elastic Foundation - Rahul Kumar; Chandan Kumar; Mukesh Singh; Jay Damania; Jigyasa Singh; Jeeoot Singh (Mechanics of Advanced Composite Structures)
This study explores the bending analysis of porous functionally graded material (FGM) rectangular plate resting on two parameters elastic foundation based on the higher-order shear deformation theory (HSDT) and subjected to various types of transverse load.The material properties of porous FGM rectangular plates are assumed to be graded in the thickness direction according to modified power-law distribution in terms of the porosity fractions and grading index. The energy principle develops governing differential equations (GDEs) of the plate. The derived formulation is implemented numerically using the strong formulation, and the multiquadric radial basis function (MQ-RBF) based meshfree method for discretizing the GDEs. The MQ-RBF improved by modifying the radial distance between the interpolation. A code has been developed in MATLAB (2019) to obtain the results. The influence of the span to thickness ratio, aspect ratio, transverse loading type, porosity fraction, grading index, and elastic foundation coefficients on the bending response of porous FGM rectangular plate. New numerical results can provide benchmarks for future analyses of porous FGM plates on elastic foundations.